A study of collocational competence of Malay students in their english speaking proficiency - Arifuddin bin Abdullah (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
This study aims to investigate students' collocational competence by examining the relationship between the knowledge of lexical collocation and their speaking proficiency as well as identify the patterns of collocational mis(use) among them. The respondents involved comprised 30 students of Universiti Malaysia Kelantan (UMK). A lexical collocation test (LCT) was constructed to gauge the knowledge of collocation, while a speaking proficiency test (SPT) adopted from the IEL TS was administered to determine the students' level of speaking proficiency. Both variables were then correlated. The result indicates that there was no significant correlation between the knowledge of collocation and speaking proficiency among the respondents. This study also reveals that the majority of the respondents did not perform well in LCT. On the patterns of errors made, the scores on LCT reveal that the respondents struggled with the Nounl+of+Noun2 and Verb+Adverb categories. However, they performed well in the Verb+Noun and Adjective+Noun categories. Besides, the data from the speaking proficiency test point out that miscollocation mostly occurred in the Verb+Noun and Adjective+Noun categories. Based on the findings, it is revealed that exposure to the target language plays a vital role in language acquisition. Exposure to collocations in particular would enable the learners to speak more fluently and sound more native-like.